2006
DOI: 10.1038/sj.eye.6702234
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate excitotoxicity in glaucoma: truth or fiction? By AJ Lotery

Abstract: uninvestigated, family history and the observed phenotype makes the differential diagnoses of congenital abnormality related to choroidal inflammation, retinotoxic medication uses, infective, inflammatory, systemic metabolic or choroidal vasculopathy highly improbable.Other causes of well-defined atrophy such as this occurs in choroideremia, gyrate atrophy, and bifocal choroidal atrophy. However, none of these are consistent with this case. In summary, we present a novel lobular chorioretinal dystrophy for dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…A misconception has been that, for excitotoxicity to occur, elevated glutamate levels must be detected in the retina/ocular fluids of experimental animals or humans with glaucoma [27], [28]. Excess glutamate release is a hallmark of acute brain injuries with fast and severe neural tissue damage [29], but this is not necessarily characteristic of a slow, progressing neurodegenerative disease such as glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…A misconception has been that, for excitotoxicity to occur, elevated glutamate levels must be detected in the retina/ocular fluids of experimental animals or humans with glaucoma [27], [28]. Excess glutamate release is a hallmark of acute brain injuries with fast and severe neural tissue damage [29], but this is not necessarily characteristic of a slow, progressing neurodegenerative disease such as glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although an elevation of glutamate concentration in the vitreous humor was reported [89, 90], the following studies could not reproduce these results [91–94]. However, an elevation in the glutamate level in the vitreous humor is not necessary to induce excitotoxicity in the experimental animals or humans with glaucoma [95, 96]. It is because glutamate increase is likely to occur only in localized areas of the retina or optic nerve at any one time during glaucomatous neurodegeneration.…”
Section: Abnormalities Of Glutamate Metabolismmentioning
confidence: 99%
“…12 Among these hypotheses, evidence regarding the role of glutamate in RGC death has been controversial, and, to date, the role of increased levels of glutamate in RGC death in glaucomatous damage has never been substantiated. 13,14 However, after inducing excitotoxicity by N-methyl-D-aspartic acid (NMDA) or kainic acid (KA), a number of studies on rodents and primates have shown that excitotoxicity does play a role in the death of RGCs because antagonists against NMDA and non-NMDA receptors have been shown to offer neuroprotection. [15][16][17][18] Although studies in animal models of excitotoxicity have shown that NMDA, and non-NMDA receptor antagonists offer neuroprotection, the underlying mechanisms are still not well understood.…”
mentioning
confidence: 99%